Absorption, metabolism and excretion of [14C]gemigliptin, a novel dipeptidyl peptidase 4 inhibitor, in humans. (June 2014) - Kim, Namtae; Patrick, Lorna; Mair, Stuart; Stevens, Lloyd; Ford, Gill; Birks, Vicky; Lee, Sung-Hack
Abstract 1. Gemigliptin (formerly known as LC15-0444) is a newly developed dipeptidyl peptidase 4 inhibitor for the treatment of type 2 diabetes. Following oral administration of 50 mg (5.4 MBq) [14C]gemigliptin to healthy male subjects, absorption, metabolism and excretion were investigated. 2. A total of 90.5% of administered dose was recovered over 192 hr postdose, with 63.4% from urine and 27.1% from feces. Based on urinary recovery of radioactivity, a minimum 63.4% absorption from gastrointestinal tract could be confirmed. 3. Twenty-three metabolites were identified in plasma, urine and feces. In plasma, gemigliptin was the most abundant component accounting for 67.2% ∼ 100% of plasma radioactivity. LC15-0636, a hydroxylated metabolite of gemigliptin, was the only human metabolite with systemic exposure more than 10% of total drug-related exposure. Unchanged gemigliptin accounted for 44.8% ∼ 67.2% of urinary radioactivity and 27.7% ∼ 51.8% of fecal radioactivity. The elimination of gemigliptin was balanced between metabolism and excretion through urine and feces. CYP3A4 was identified as the dominant CYP isozyme converting gemigliptin to LC15-0636 in recombinant CYP/FMO enzymes.